2019
DOI: 10.1007/s00244-019-00662-5
|View full text |Cite
|
Sign up to set email alerts
|

Methods of Assessment of Metal Contamination in Bottom Sediments (Case Study: Straszyn Lake, Poland)

Abstract: The concentrations of six metals (Zn, Cu, Pb, Ni, Cr, and Cd) were investigated in bottom sediments of Straszyn Lake (North Poland). This study was designed to determine a total content of metals and to assess their mobility and bioavailability. The sequential extraction was used to fractionate metals into five fractions: exchangeable, bound to carbonates, bound to Fe–Mn oxides, bound to organic matter, and residual. The evaluation of sediments contamination degree by metals was performed by applying the geoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 56 publications
4
20
0
Order By: Relevance
“…The C:N ratio is higher (greater than 20) in macrophytic and cellulose-rich terrestrial organic matter and lower (between 4 and 10) in algae and phytoplankton [27]. Similar results (from 5.36 up to 10.41) were obtained by Small et al [26] who examined this parameter in two dam reservoirs in Poland (Zemborzycki and Brody Iłżeckie Reservoirs).…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…The C:N ratio is higher (greater than 20) in macrophytic and cellulose-rich terrestrial organic matter and lower (between 4 and 10) in algae and phytoplankton [27]. Similar results (from 5.36 up to 10.41) were obtained by Small et al [26] who examined this parameter in two dam reservoirs in Poland (Zemborzycki and Brody Iłżeckie Reservoirs).…”
Section: Resultssupporting
confidence: 83%
“…Low concentrations of sedimentary organic carbon in the southern part of the reservoir may be ascribed then to the lower depth and higher water dynamics than other areas. Weaker accumulation of organic matter in the shallow water zone and in the zone of higher water dynamics were confirmed by a number of authors [14,20,22,25,27,36].…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…It has been observed that to define more accurately the quality of sediments potentially affected by heavy metals and pollutants, a correct option could be an intensive comparison of applied sediment quality guidelines (SQGs) (Burton 2018;Birch 2018;Liu et al 2019;Jones et al 2019). Comparative evaluations of different SQGs for contaminants, in order to obtain an environmental quality and risk assessment of internal waters, has been intensively provided in recent years (Ali et al 2016;Baran et al 2016;Bhateria and Jain 2016;Gopal et al 2017;Strady et al 2017;Xu et al 2017;Shyleshchandran et al 2018;Zhao et al 2018;Aung et al 2019;Kulbat and Sokołowska 2019;Christophoridis et al 2020). It has to be noted that SQGs for the assessment of sediment quality are very different across the different countries.…”
Section: Discussionmentioning
confidence: 99%
“…Freshwater reservoirs role great importance for investigating pollution as they are generally located close to the urban and industrial sources of pollution, where contamination issues are most likely to arise (Ammar et al 2015; Baran et al 2016). The reservoir sediments can be sensitive indicators for monitoring contaminants in aquatic environments (Liu et al 2018;Aung et al 2019;Kulbat and Sokołowska 2019;Zhuang et al 2019), acting as sinks for different pollutants. In particular, clay fraction is mainly enriched of heavy metals, especially in highly polluted sediments (Uddin 2017;Jones et al 2019).…”
Section: Introductionmentioning
confidence: 99%